Trends in Corpus Linguistics Research: A Bibliometric Analysis (2004-2024) - Varia Virdania Virdaus; Gunarti Dwi Lestari; Wiwin Yulianingsih; Rofik Djalal Rosyanafi; Muchamad Arif; Hamidah Binti Mohamad (The Indonesian Institute of Science and Technology Research, 2026)
This bibliometric study analyzes changes in corpus linguistics research from 2004 to 2024, emphasizing discourse analysis, digital literacy, and educational technology. Despite being the crucial tool for language analysis, corpus linguistics is frequently not taught in teacher preparation programs. Literacy has evolved digitally as a result of the growing prevalence of computers and the internet. Research indicates that educators must improve their technological proficiency. Using an analysis of 128 papers from the Scopus database, this study looks at the gaps in the extensive body of scientific literature on corpus linguistics. Studies indicate that scientific output has increased significantly in recent years, particularly since 2018. Papers are currently the most widely used publication format. The United States excels at assisting and cooperating with other nations. According to the investigation, Robert C. Meurant and Rodney H. Jones were the primary authors and had the highest number of citations and contributions, respectively. Traditional language methods are no longer the main focus of research; instead, an interdisciplinary framework that combines digital technology and education has taken its place. As a result, there is now a close connection between instruction and online and data resources. According to the research, literacy in corpus linguistics is now seen as a skill influenced by contemporary teaching strategies, the accessibility of data, and student engagement in the classroom.